DEFINITION OF FUNDAMENTAL BREACH OF CONTRACT OF INTERNATIONAL SALE OF GOODS - Zdravkovic, Uros (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
The fundamental breach of contract is defined by the article 25 of the CISG which states: “A breach of contract committed by one of the parties is fundamental if it results in such detriment to the other party as substantially to deprive him of what he is entitled to expect under the contract, unless the party in breach did not foresee and a reasonable person of the same kind in the same circumstances would not have foreseen such a result.”When fundamental breach of contract occurs, deprived party (seller or buyer) has a right to avoid a contract. Avoidance of contract is remedy of last resort, in the situation when other remedies are ineffective.For existence of fundamental breach of contract, on the basis of the article 25 of the CISG, there are two criteria which must be fulfilled. First criterion is of objective nature and comprises two conditions: a) breach of obligation defined in contract or in the CISG and b) such breach substantially deprives other party of what she is entitled to expect under the contract. Second criterion is subjective: the breaching party needs to foresee that result. This criterion has also objective element, through the usage of the standard of reasonable person. Hence, even in situation when breaching party did not foresee substantial deprivation of other party as a result of its breach, it will be considered that substantial breach of contract exist if reasonable person of the same kind in the same circumstances would foreseen such a result.
Keywords: fundamental breach of contract; contract of international sales of goods; CISG; avoidance of contract